Cardiorespiratory demands during an inline speed skating marathon race: a case report - Stangier, C.; Abel, T.; Mierau, J.; Hollmann, W.; Strüder, H. K. (The Journal of Sports Medicine and Physical Fitness, 2016)
This study was designed to investigate the intensity profile during an inline speed skating marathon road race. A highly-trained male athlete (20 y, 73.4 kg, 178 cm, VO2 peak: 60.8 mL/kg·min) participated in a marathon road race. Oxygen uptake (VO2), respiratory exchange ratio (RER), heart rate (HR) and speed were measured using a portable gas analysis system with a HR monitor and GPS-Sensor integrated. The athlete´s peak VO2, HR and speed at ventilatory thresholds were assessed during an incremental field test (22 km/h, increase 2 km/h every 5 min) one week before the race. During the race, the absolute time spent in the "easy intensity zone" (V?O2 below VT1) was 1 min, 49 min "moderate intensity zone" (VO2 between VT1 and VT2), and 26 min in the "hard intensity zone" (VO2 above VT2). The average HR was 171±6 bpm, corresponding to 95% of the maximum. This study shows that inline speed skating road races over a marathon are conducted at moderate to high VO2 and heart rate levels. The physiological racing pattern is very intermittent, requiring both a high level of aerobic and anaerobic capacity.